2021
DOI: 10.1111/jvim.16038
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and carriage of multidrug‐resistant organisms in dogs and cats presented to small animal practices and clinics in Switzerland

Abstract: Background: The emergence and spread of multidrug-resistant organisms (MDRO) present a threat to human and animal health. Objectives: To assess acquisition, prevalence of and risk factors for MDRO carriage in dogs and cats presented to veterinary clinics or practices in Switzerland. Animals: Privately owned dogs (n = 183) and cats (n = 88) presented to 4 veterinary hospitals and 1 practice. Methods: Prospective, longitudinal, observational study. Oronasal and rectal swabs were collected at presentation and 69%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 67 publications
(174 reference statements)
0
24
0
Order By: Relevance
“…At presentation of their animal to a veterinary clinic or practice owners were invited to participate in the study by filling in a pet-centered and owner-centered risk-factor questionnaire and by submitting nasal swabs and fecal samples for culture. In addition, their dogs and cats were sampled via oro-nasal and rectal swabs at presentation and discharge from the veterinary hospitals as previously described [ 11 ]. If either owner or pet carried a MDRO, owners were invited to participate in a follow-up study, which foresaw monthly resampling until at least two negative results had been obtained.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…At presentation of their animal to a veterinary clinic or practice owners were invited to participate in the study by filling in a pet-centered and owner-centered risk-factor questionnaire and by submitting nasal swabs and fecal samples for culture. In addition, their dogs and cats were sampled via oro-nasal and rectal swabs at presentation and discharge from the veterinary hospitals as previously described [ 11 ]. If either owner or pet carried a MDRO, owners were invited to participate in a follow-up study, which foresaw monthly resampling until at least two negative results had been obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Five owner-cat pairs and 16 owner-dog pairs were followed to monitor for co-colonization. The part of this study in the grey box has been previously reported [ 11 ]. Abbreviations: MDROs, multidrug-resistant organisms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…in Salmonella Heidelberg. This presents a potential threat of introduction of this vertically transmitted organism into the EU poultry production environment via escape of organisms from processing waste or from infected humans, or pets consuming raw meat based foods (Souza et al., 2020; Dazio et al., 2021). A recent international Salmonella outbreak caused by powdered egg and linked to persistent contamination of a spray drying machine also illustrates the role of post‐harvest contamination of the processing environment (Labska et al., 2021).…”
Section: Assessmentmentioning
confidence: 99%